VCP controls KCC2 degradation through FAF1 recruitment and accelerates emergence from anesthesia - Peng Chen; Jiang-Jian Hu; Yuexin Liu; Boxu Cao; Xue-Jun Song (Proceedings of the National Academy of Sciences, 2025)
Ubiquitin-proteasomal degradation of K + /Cl − cotransporter 2 (KCC2) in the ventral posteromedial nucleus (VPM) has been demonstrated to serve as a common mechanism by which the brain emerges from anesthesia and regains consciousness. Ubiquitin-proteasomal degradation of KCC2 during anesthesia is driven by E3 ligase Fbxl4. However, the mechanism by which ubiquitinated KCC2 is targeted to the proteasome has not been elucidated. We report in cultured neuro-2a cells that the valosin-containing protein (VCP) transported ubiquitinated KCC2 to the proteasome and in mice in vivo experiments that inhibition of VCP restored KCC2 expression in the VPM and enhanced the effects of anesthesia. In cultured neuro-2a cells, propofol-induced degradation of KCC2 was inhibited by VCP inhibitor DBeQ and VCP knockout plasmid sgRNA(VCP). Propofol-induced enhanced interaction between VCP and KCC2 was inhibited by knockout of Fbxl4 or Fas-associated factor 1 (FAF1). In in vivo studies, pharmacological or genetic inhibition of VCP in the VPM significantly prevented KCC2 degradation and enhanced propofol anesthesia; these effects were abrogated by a KCC2 antagonist VU0463271. These results demonstrate that the VCP controls ubiquitin-proteasomal degradation of KCC2 dependent on FAF1 recruitment and serves as a mechanism for the ubiquitin-proteasomal degradation of KCC2, which is responsible for the subsequent emergence from anesthesia.